Kesesuaian Kampung Batik Laweyan sebagai Klaster Industri Kreatif Ditinjau dari Keterkaitan Spasial dan Fungsional - Safitri, Afinda Nurul; Aliyah, Istijabatul; Mukaromah, Hakimatul (LPPM Universitas Terbuka, 2025)
The tradition of batik making that grows in villages has given rise to the phenomenon of batik villages. Kampung Batik Laweyan is one of the batik centers in Surakarta City that has existed since 1546. Starting from the understanding that the cluster approach is a solution to increase the competitiveness of the batik creative industry, by taking the study location in Kampung Batik Laweyan, this study aims to determine the suitability of Kampung Batik Laweyan as a creative cluster industry. This research was conducted using quantitative methods, by using scoring analysis techniques. Data were collected through field observations, interviews, and questionnaires. The results of the study showed that Kampung Batik Laweyan has a score of 1 and is classified as quite suitable as a creative cluster industry. The strength of Kampung Batik Laweyan is in the inter-industry linkages and cooperation with external institutions. Meanwhile, the factor that needs to be improved is internal cooperation between batik industries. Based on these findings, it is hoped that closer cooperation can be established between batik industries in Kampung Batik Laweyan, which can be initiated by the community or city government.